Systematic review-meta-analysis of the effect of chilling on Campylobacter spp. during primary processing of broilers. (October 2015) - Bucher, Oliver; Waddell, Lisa; Greig, Judy; Smith, Ben A.
Abstract: Carcass chilling is a critical control point for Campylobacter spp. during the primary processing of broiler chickens. Our objective was to evaluate chilling intervention research that measured the change in Campylobacter prevalence and concentration on broiler chicken carcasses during primary processing using systematic review-meta-analysis (SR-MA) methodology. Experimental and observational research published in English that investigated impacts of chilling on Campylobacter spp. during primary processing of broiler chicken carcasses were considered. Random-effects MA of air chilling resulted in heterogenous summary effect estimates (mean reduction = 0.74 log10 CFU/carcass, 95% CI: 0.32–1.17, I 2 = 91.3%; and odds ratio = 7.42, 95% CI: 0.32–174.05, I 2 = 92.3%). Random-effects MA of immersion chilling with chlorine resulted in heterogenous summary effect estimates (mean reduction = 1.74 log10 CFU/carcass, 95% CI: 1.32–2.16, I 2 = 86.4%; and odds ratio = 0.50, 95% CI: 0.20–1.28, I 2 = 90.6%). Effects of immersion chilling with unspecified disinfectants were also determined and varied depending on study design. The SR-MA indicated that air chilling and immersion chilling reduce Campylobacter concentrations. Due to conflicting results across studies, the estimated average effect of air chilling on Campylobacter prevalence is not informative. Immersion chilling with chlorine demonstrated a trend towards reduced Campylobacter prevalence, but this result was not significant; results should be interpreted with caution because the overall methodological soundness of included studies was low. Existing research on the effectiveness of broiler carcass chilling on Campylobacter concentration or prevalence is limited and heterogenous. Results generated herein can inform decisions makers and stakeholders on potential effective chilling interventions, and can be used to inform quantitative microbial risk assessment to estimate processing measure impacts on public health. Highlights: SR-MA was used to evaluate chilling impacts on Campylobacter on poultry carcasses. Air chilling and immersion chilling indicate reduced Campylobacter concentrations. Air chilling impact on Campylobacter prevalence is ambiguous. Immersion chilling with chlorine indicates reduced Campylobacter prevalence. Results were limited and mostly heterogenous; more research is needed.